Mathematical simulation of low-temperature gas separation; Petroleum and Coal; Vol. 59, iss. 2 - Bunaev A. A. Ayur Alekseevich; Dolganov I. M. Igor Mikhailovich; Dolganova I. O. Irena Olegovna; Vladesku A. Alina (2016, 2016)
Title screen